PENERAPAN PERMAINAN LABIRIN UNTUK MENINGKATKAN KONSENTRASI PADA ANAK ADHD (ATTENTION DEFICIT HYPERACTIVITY DISORDER) DI SLB BUKESRA BANDA ACEH - Intan Yolanda; Syaiful Bahri; Fajriani Fajriani (Program Studi Bimbingan dan Konseling, FKIP Universitas Syiah Kuala, 2019)
The concentration of learning is a focused attention during the learning process and it facilitates the understanding of lessons explained by the teacher so that it can support student’s achievement. Learning concentration is called effective when it is characterized by the strength of memories possessed by individuals. This study aimed to see the effectiveness of the labyrinth game in improving the learning concentration of children with ADHD using a quantitative descriptive approach and the type of single-subject experimental design with the A-B-A design baseline logic. The subjects in this study were 3 students of Bukesra SLB Banda Aceh with low learning concentration. The instrument used in this study was the concentration scale. Data analysis techniques used in this research was data analysis in conditions and data analysis between conditions. The results of the study showed that the students’ learning concentration after being given the treatment of the labyrinth game was higher than their learning concentration before being given the treatment. This is supported by the results of data analysis on the level changes in condition with an increase in the intervention phase (B) was (+6) at AP, (+9) at MH, (+8) at AM and the baseline phase (A2) was (+8) at AP, (+8) at MH, (+8) at AM. The results of data analysis between conditions in all phase comparisons showed the percentage of overlap below 90%. Data analysis between conditions on observation’s results showed a percentage of 0% at AP, 0% at MH, and 0% at AM in a comparison of baseline (A1) with intervention (B) and baseline (A2). So that it can be concluded that there was a significant increase between the students’ learning concentration after being given treatment and the analysis results of observational data obtained a tendency toward positive direction and trace data or increasing the percentage of the three subjects.Keywords: ADHD Children, Labyrinth Game, Improving Concentration, Research single-subject experimental design, A-B-A design baseline logic. Abstrak: Konsentrasi belajar adalah terfokusnya perhatian pada saat proses pembelajaran yang memudahkan memahami pelajaran yang dijelaskan guru sehingga dapat menunjang prestasi siswa. Konsentrasi belajar dikatakan efektif ditandai dengan kuatnya ingatan yang dimiliki oleh individu. Penelitian ini bertujuan untuk melihat keefektifan permainan labirin dalam meningkatkan konsentrasi belajar anak ADHD dengan menggunakan pendekatan deskriptif kuantitatif dan jenis penelitian single-subject experimental design baseline logic desain A-B-A. Subjek dalam penelitian ini adalah 3 orang siswa ADHD dari SLB Bukesra Banda Aceh dengan konsentrasi belajar rendah. Instrumen yang digunakan dalam penelitian ini adalah skala konsentrasi. Teknik analisis data menggunakan analisis data dalam kondisi dan analisis data antar kondisi. Hasil penelitian diperoleh bahwa konsentrasi belajar siswa setelah diberikan perlakuan permainan labirin lebih tinggi dari konsentrasi belajar siswa sebelum diberikan perlakuan. Hal ini didukung oleh hasil analisis data pada perubahan level dalam kondisi dengan level peningkatan pada fase intervensi (B) yaitu (+6) pada AP, (+9) pada MH, (+8) pada AM dan fase baseline (A2) yaitu (+8) pada AP, (+8) pada MH, (+8) pada AM. Hasil analisis data antar kondisi pada semua perbandingan fase menunjukkan persentase overlap dibawah 90%. Analisis data antar kondisi pada hasil pelaksanaan observasi menunjukkan persentase 0% pada AP, 0% pada MH, dan 0% pada AM pada perbandingan fase baseline (A1) dengan intervensi (B) dan baseline (A2). Sehingga dapat disimpulkan bahwa terdapat peningkatan yang signifikan antara konsentrasi belajar siswa setelah diberikan perlakuan dan hasil analisis data observasi diperoleh kecenderungan arah dan jejak data yang bersifat positif atau semakin meningkat persentase ketiga subjek.Kata kunci: Anak ADHD, Labirin, Konsentrasi, single-subject experimental design, baseline logic desain A-B-A.